Determination Methods and Influencing Factors of Grain Mechanical Properties - Peng Gao; Shuangqi Tian; Xing’ao Xue; Jing Lu (Journal of Food Quality)
Grain is extremely vulnerable to external loads during production and processing, resulting in the deterioration of grain quality. Deteriorated grain not only affects the economic value of grain but also affects the safety of storage. This has a very important relationship with the biomechanical properties of grains. It is of great significance to explore the mechanical properties of grain under different conditions and analyze the relationship between its physical and chemical properties and mechanical properties for improving its processing and eating quality. In this paper, the research methods of the mechanical properties of grains are reviewed. Various factors influencing the mechanical properties of cereals were analyzed. The relationship between the internal organizational structure of grain and its mechanical properties was discussed. This paper puts forward the shortcomings in the current research on the mechanical properties of grains and puts forward the prospect and analysis of its importance in future development in order to provide a reference for reducing crushing in the grain processing process.